2016
DOI: 10.1002/app.44582
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Kraft lignin as a method to improve structural and mechanical properties of lignin‐polyethylene blends

Abstract: Lignin is a promising candidate for blends with thermoplastic polymers. Still, this endeavour is a challenge due to poor compatibility between both components. In this article, the effect of lignin esterification on the improvement of the compatibility between hardwood Kraft lignin and high‐density polyethylene (PE‐HD) is investigated. For this purpose, lignin was esterified with acetic, propionic, and butyric anhydride; its amount in the blends varied from 10 to 40%. Light microscopic images of blends show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
(76 reference statements)
1
28
0
Order By: Relevance
“…Lignin esterification has been studied as a strategy to improve compatibility between lignin and polyolefins in blends and composites [ 46 , 65 , 91 , 92 ]. Figure 9 shows the esterification of lignin by acetic anhydride.…”
Section: Lignin Modificationmentioning
confidence: 99%
“…Lignin esterification has been studied as a strategy to improve compatibility between lignin and polyolefins in blends and composites [ 46 , 65 , 91 , 92 ]. Figure 9 shows the esterification of lignin by acetic anhydride.…”
Section: Lignin Modificationmentioning
confidence: 99%
“…It was observed that the tensile strength of the composites decreased with lignin loading. The tensile strength of composites also decreased with increasing filler content in thermoplastics, 42 and in biodegradable polymers such as PLA 43,44 and PBS. 10,45 Interestingly, both lignin imparted similar effect on the mechanical properties of the composites.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Saake et al. found that esterification on lignin was useful to improve the mechanical performance of lignin/HDPE composites, and the longer the alkyl chain segments, the better the compatibility . In addition, the compatibility can be further improved by reducing the lignin particle size .…”
Section: Introductionmentioning
confidence: 99%